Monitoring the impact of COVID-19 in Myanmar: Agricultural commodity traders - Synopsis of results from three survey rounds through early August 2020 - Goeb, Joseph; Zu, A Myint; Zone, Phoo Pye; Synt, Nang Lun Kham; Boughton, Duncan; Maredia, Mywish K. (International Food Policy Research Institute, 2020)
To understand how Myanmar’s crop marketing system has been affected by the COVID-19 crisis, phone interviews were conducted with more than 100 agricultural commodity traders roughly every 30 days from late May until early August 2020. A round of qualitative interviews was also conducted with key informants on land-trading routes to China, Thailand, and India. Key findings • Traders who reported that the pandemic is affecting their business in any way declined from 77 percent in late May to 43 percent in early August. Buying and marketing challenges were the most common disruptions reported in early August, followed by difficulties in collecting repayments on credit lent out to farmers. Increasing numbers of traders also reported difficulties in obtaining new loans or credit for their business. • Higher shares of traders reported year-on-year decreases both in credit provision and in wholesale trading volumes in August compared to June. • More traders report a decrease in competition than an increase since the crisis began. • Crop buying and selling prices have been stable on average between April and August. • Border gate closures at the China (Muse), Thailand (Myawaddy), and India (Tamu) borders have resulted in drastic reductions in overland exports of agricultural commodities since March 2020. Key informants said that there has been almost no crop trading to China and India, while exports to Thailand are down over half compared to a year ago. Recommended actions • Coordinate domestic transport restrictions put in place in response to the recent second wave of COVID-19 to allow continued domestic trade of agricultural commodities. • Facilitate safe exports of agricultural commodities. This should be done with formal agreements and government investments in monitoring and infrastructure. If borders remain closed into the monsoon harvest season later in 2020, farmers should expect to receive poor prices for their crops. • Quickly expand the provision of loans for working capital to crop traders (CERP Action 2.1.1). This will enable traders to continue their buying activities through the coming harvest and prevent a possible decline in competition in the sector. • Continue the waiver of the 2 percent withholding tax for crop traders (CERP Action 2.1.3).